Relation of MPO, MnSOD, NQO1 gene variants in endometrial carcinoma in the line of PCR-RFLP methods - Bulgurcuoglu Kuran, Sibel; Iplik, Elif Sinem; Cakmakoglu, Bedia; Timirci Kahraman, Ozlem; Iyibozkurt, Ahmet Cem; Koc, Arzu; Ergen, Arzu; Gulec Yilmaz, Seda; Isbir, Turgay (Cellular and Molecular Biology, 2018)
Reactive oxygen species (ROS) have been shown to be responsible for inducing DNA damage leading to mutagenesis, carcinogenesis, and cell death if the capacity of the protective antioxidant system is impaired. Endometrial carcinoma is the primary cancer type in the female genital system. The enhanced cell lipid peroxidation and impaired antioxidant enzyme activities observed in patients with endometrial cancer indicate the potential for oxidative injury to cells and cell membranes in such patients. The aim of the study was to investigate the possible association between gene variants of superoxide dismutase (SOD), myeloperoxidase (MPO), and NADPH quinone oxido reductase (NQO1), and their possible role in endometrial cancer in Turkish patients. According to results, MPO G+ genotype and AG genotype were significantly increased in patients compared with controls (P<0.001). We suggest that the MPO polymorphism might be a risk for endometrial cancer.